‘Disabled access’: debating the accessibility of Zimbabwe national museums by people with disabilities - Simbarashe Shadreck Chitima; Paul Mupira (Langaa RPCIG, 2023)
Persons with disabilities (PWDs) are one of the most segregated, stigmatised, marginalised and devalued groups in society. They have been categorised as ‘deviant’, ‘sub-human’ or ‘diseased organisms’ in many societies. Museums can impact positively on the lives of people with disabilities, act as a catalyst of social inclusion, a vehicle for empowerment, and generally contribute towards the creation of more equitable societies. The chapter examines the provision of disabled access in museums in Zimbabwe in terms of international best practices, as well as opportunities for access improvements. Using qualitative and phenomenological approaches, the research gathered that people with disabilities are a heterogeneous group that experience different degrees of exclusion to and in museums. PWDs face environmental, attitudinal, financial, intellectual, and cultural barriers in accessing museums in Zimbabwe. This situation is typical of the five national museums in Zimbabwe. The study concludes that museums in Zimbabwe are violating the cultural rights of PWDs and perpetuating their marginalisation and segregation. Museums, it concludes, need to put in place access policies that are in line with the new Constitution of Zimbabwe and international best practices in order to improve the access opportunities for all people with disabilities.